Implementasi Etika Islam: Upaya Revitalisasi Etika Aparatur Birokrasi sebagai Penyelenggara Pelayanan Publik - Hidayat, Rahmat; Setiabudi, Adi; Nuriman, Eki Jaki; Dewi, Maya Puspita; Muksin, Nani Nuraini (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Public service ethics for bureaucratic apparatuses could play a role in determining success in carrying out duties as public service providers in the government system in Indonesia.This research aims to provide an overview and solution of various ethical problems of bureaucrats that have been known as the pathology of government or bureaucracy. The implementation of Islamic ethics in the bureaucratic body could be a way to encourage better behavior among bureaucrats, who sometimes don't seem to be following the rules and authority as public servants. There are also problems with arrogance and a lack of attention to detail among some bureaucrats, as well as problems with maladministration, widespread corruption, and law enforcement abusing their authority. This research was conducted using a descriptive qualitative approach, which entailed a thorough review of literature on the subject. The author extracted information on the issue of violations of the behavior of state apparatus that still often occur in Indonesia. This was supported by sources from credible news outlets and scientific journal articles, survey data from official government websites, and relevant books.This research draws upon existing data. In the spirit of continuous improvement and accountability, it is essential for the bureaucratic apparatus to recognize the profound responsibility entrusted by the community and the state as protectors of society. The mandate of the bureaucracy is not merely a symbol of social relations among humans, but also an accountability to God.